Zinc modified mesoporous Y-type molecular sieve, electrochemical sensor, preparation method of molecular sieve and application of molecular sieve in detection of acetaminophen content

By performing zinc modification treatment on mesoporous Y-type molecular sieve, the problems of complex equipment, high cost and poor sensitivity of acetaminophen detection in the prior art are solved, and electrochemical sensors with high accuracy and sensitivity are realized. In drug quality monitoring.

CN119284920AActive Publication Date: 2025-01-10GUANGDONG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411312582.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-10
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing acetaminophen detection technology has problems such as complex equipment, high cost, low accuracy and poor sensitivity, especially in mesoporous Y-type molecular sieve applications with poor detection accuracy and sensitivity.

Method used

The new template agent Bola type surfactant combined with a specific proportion of raw materials were prepared by preparing zinc-modified mesoporous Y-type molecular sieve, and modified by metal zinc to enhance its specific surface area, adsorption capacity and conductivity, and is used to build an electrochemical sensor to improve detection Accuracy and sensitivity.

Benefits of technology

The high accuracy, sensitivity and wide range detection of acetaminophen are achieved, which reduces detection costs and improves the detection sensitivity and stability of electrochemical sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284920A_ABST
    Figure CN119284920A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a zinc modified mesoporous Y type molecular sieve. The preparation method comprises the following steps: preparing a mesoporous NaY type molecular sieve by taking a Bola type surfactant [C5H5-N < + >-(CH2) 10-O-(p-C6H4) 2-O-(CH2) 10-N < + >-C5H5]. 2 [Br <->] as a template agent and matching with a specific raw material proportion; the NaY type molecular sieve is sequentially soaked in an ammonium salt solution and a zinc salt solution for ion exchange, and after drying and calcination, the zinc modified mesoporous Y type molecular sieve is obtained. The zinc-modified mesoporous Y-type molecular sieve prepared by the invention has larger specific surface area, higher pore volume and excellent conductivity, the detection range of the zinc-modified mesoporous Y-type molecular sieve applied to an electrochemical sensor for detecting the content of acetaminophen is 0.066-10000 [mu] mol / L, the detection limit can reach 0.01 [mu] mol / L, meanwhile, the zinc-modified mesoporous Y-type molecular sieve has excellent detection sensitivity, stability, reproducibility and selectivity, and the application prospect is wide. Accurate determination of acetaminophen in drugs can be achieved, and the prepared electrochemical sensor is simple in structure, convenient to operate and low in detection cost and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical sensors, and specifically relates to a zinc-modified mesoporous Y-type molecular sieve, an electrochemical sensor, a preparation method thereof, and application in detecting acetaminophen content. Background Art

[0002] Acetaminophen (PC), also known as paracetamol, is an organic compound (chemical formula: C8H9NO2) and a commonly used antipyretic and analgesic. It is mainly used for fever caused by the common cold or influenza, and is also used to relieve mild to moderate pain such as headache, joint pain, migraine, toothache, muscle pain, neuralgia, dysmenorrhea, etc. It is recognized by the international medical community as the safest and most effective common medicine for the human body. Although the reasonable dosage of PC (0.3-0.5g for adults at a time, not more than 2g per day) is safe and effective, taking too little PC will not reach the minimum dosage for treating the above diseases, affecting the medical effect, and excessive and long-term continuous use of PC will produce serious side effects. At the same time, the secretion disruptors caused by the drug will affect the endocrine system of the human body. For example, high doses of PC will lead to the accumulation of toxic metabolites, leading to liver toxicity or kidney toxicity, and other organ systems such as hearing and brain may also be affected. Therefore, developing a simple, sensitive and low-cost technology to detect the content of acetaminophen in drugs has important practical significance for the quality monitoring of acetaminophen in various drugs in the pharmaceutical industry.

[0003] There are many methods for detecting acetaminophen content, all of which have certain advantages and disadvantages. For example, the common spectrophotometry (UV-Vis) method for determining PC content is simple to operate and has a wide detection range, but it has low accuracy and poor sensitivity; nuclear magnetic resonance (NMRS) is often used for qualitative analysis of PC, which can determine its molecular structure and charge distribution, but cannot be quantitatively analyzed; liquid chromatography (HPLC) is more accurate than the previous methods, but it is time-consuming, labor-intensive, and expensive; capillary electrophoresis (HPCE) has the advantages of diverse operating modes and small injection volume, but it is also time-consuming, labor-intensive, and expensive. The above methods not only have high requirements on instruments, but also the pre-treatment of samples is more troublesome, which is not convenient for real-time monitoring.

[0004] Electrochemical sensors can quickly and sensitively detect target information, and then directly or indirectly convert the target information into electrical signals, thereby achieving qualitative and quantitative analysis of the target. They have the advantages of high sensitivity, simple structure, and low price, and have good development prospects in the field of analysis and detection. The sensitivity of electrochemical sensors mainly depends on the performance of the sensitive element. The sensitivity, detection limit, and detection range of electrochemical sensors currently used to detect acetaminophen need to be improved.

[0005] Y-type mesoporous molecular sieve has good hydrothermal stability, unique pore structure and high specific surface area, and is an ideal matrix material for constructing electrochemical sensors. The detection performance of electrochemical sensors is closely related to the surface area, pore volume and conductivity of molecular sieves. Templates play a vital role in the synthesis of molecular sieves. They can regulate the specific surface area of ​​molecular sieve materials by regulating the crystallinity of molecular sieves and the structure and size of the pores. The specific surface area and pore volume of mesoporous Y-type molecular sieves prepared by templates used in the prior art are still insufficient, so that their application in electrochemical sensors for detecting acetaminophen has the defects of unsatisfactory detection accuracy and detection sensitivity. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the defects and shortcomings of the existing acetaminophen detection technology, such as complex equipment, high detection cost, low detection accuracy and poor detection sensitivity, and provide a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The method adopts a new template agent and a specific template agent dosage to prepare the Y-type molecular sieve and performs metal zinc modification on the Y-type molecular sieve, so that the prepared zinc-modified mesoporous Y-type molecular sieve has the characteristics of large specific surface area, high adsorption capacity and good conductivity. The zinc-modified mesoporous Y-type molecular sieve is applied to an electrochemical sensor for detecting the content of acetaminophen to achieve the effects of high detection accuracy, high detection sensitivity and wide detection range, and the prepared electrochemical sensor has a simple structure, is convenient to operate and has a low detection cost.

[0007] The second object of the present invention is to provide a zinc-modified mesoporous Y-type molecular sieve.

[0008] A third object of the present invention is to provide an electrochemical sensor.

[0009] The fourth object of the present invention is to provide an application of an electrochemical sensor in detecting the content of acetaminophen.

[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0011] A method for preparing a zinc-modified mesoporous Y-type molecular sieve comprises the following steps:

[0012] S1. The silica sol, sodium aluminate, pH regulator and template are mixed in water to obtain an aluminosilicate gel, wherein the template is a Bola-type surfactant [C5H5-N + -(CH2) 10 -O-(p-C6H4)2-O-(CH2) 10 -N + -C5H5]·2[Br - ];

[0013] S2. The aluminosilicate gel obtained in step S1 is heated to react. After the reaction is completed, the product is collected by filtration and washing, and the product is dried and calcined to obtain a mesoporous NaY molecular sieve;

[0014] S3. The mesoporous NaY molecular sieve of step S2 is subjected to ion exchange with an ammonium salt solution to obtain an NH4Y molecular sieve; the NH4Y molecular sieve is subjected to ion exchange with a zinc salt solution, and after the reaction is completed, the precipitate is collected, dried, and calcined to obtain a mesoporous ZnY molecular sieve, which is the zinc-modified mesoporous Y molecular sieve;

[0015] Among them, the molar ratio of silica sol, sodium aluminate, pH adjuster, template agent and water in step S1 is (2-6):(0.5-3):(2-8):(0.06-0.50):(50-250).

[0016] The template agent Bola type surfactant introduced in the present invention is a long-chain amphiphilic bifunctional template agent, and the molecular structure formula is [C5H5-N+-(CH2) 10 -O-(p-C6H4)2-O-(CH2) 10 -N+-C5H5]·2[Br-], denoted as C ph-10-6 The long chains in its structure lead to the formation of mesopores, open the pores of the Y-type molecular sieve, shorten the diffusion path of the sample molecules to be detected, and reduce their diffusion resistance. ph-10-6 As a template, a Y-type molecular sieve with a mesoporous structure can be prepared in one step, greatly increasing the specific surface area and mesopore volume of the Y-type molecular sieve. At the same time, metallic zinc has good electrical conductivity. Modifying metallic zinc onto the mesoporous Y-type molecular sieve can enhance the conductivity of the molecular sieve, thereby enhancing its electrocatalytic activity as a working electrode of an electrochemical sensor.

[0017] The larger the specific surface area of ​​the molecular sieve, the higher the adsorption capacity, which can promote more active sites to participate in the reaction, allowing more target molecules to be quickly adsorbed in a short time, thereby improving the reactivity and selectivity of the molecular sieve. The appropriate ratio of silica sol, sodium aluminate, pH adjuster, template agent and water can make the prepared Y-type molecular sieve have a larger specific surface area and adsorption capacity.

[0018] Preferably, in step S1, the molar ratio of silica sol, sodium aluminate, pH adjuster, template agent and water is (3-5):(1-2):(3-6):(0.08-0.30):(80-150).

[0019] More preferably, in step S1, the molar ratio of silica sol, sodium aluminate, pH adjuster, template agent and water is 3:1:5:0.15:100.

[0020] Preferably, the pH regulator in step S1 is at least one of sodium hydroxide, potassium hydroxide and sodium bicarbonate.

[0021] Preferably, the mixing method in step S1 is magnetic stirring, the temperature of the magnetic stirring is 25 to 50° C., and the time of the magnetic stirring is 2 to 6 hours.

[0022] In the preparation of NaY molecular sieve, the appropriate reaction temperature can make the prepared Y molecular sieve have a larger specific surface area and adsorption capacity. If the reaction temperature is too high, the molecular sieve will crystallize too fast, resulting in the formation of impurity crystals; if the reaction temperature is too low, the molecular sieve will not have enough energy to grow, and the crystallization rate will be too slow, resulting in amorphous crystals, and it will be impossible to form a mesoporous Y molecular sieve with a good structure.

[0023] Preferably, the reaction temperature in step S2 is 110-150° C., and the reaction time is 24-48 hours.

[0024] Preferably, the drying temperature in step S2 is 80-120° C., and the drying time is 12-24 hours.

[0025] Preferably, the calcination temperature in step S2 is 550-600° C., and the calcination time is 5-6 hours.

[0026] Preferably, the ammonium salt of the ammonium salt solution in step S3 is at least one of ammonium chloride and ammonium nitrate.

[0027] Preferably, in step S3, the reaction temperature for ion exchange between the mesoporous NaY molecular sieve and the ammonium salt solution is 60-100° C., and the reaction time is 4-6 hours.

[0028] Preferably, the zinc salt in the zinc salt solution in step S3 is at least one of zinc chloride and zinc nitrate.

[0029] In the process of ion exchange between NH4Y molecular sieve and zinc salt solution, the appropriate zinc salt solution concentration and reaction time can make the prepared mesoporous ZnY molecular sieve have excellent conductivity and maintain a large specific surface area. If the zinc salt solution concentration is too high, it will lead to excessive blockage of the molecular sieve pores, reduce the specific surface area of ​​the molecular sieve, and thus reduce the conductivity of the molecular sieve; if the zinc salt solution concentration is too low, the zinc content of the molecular sieve after ion exchange is too low, and the conductivity is poor.

[0030] Preferably, the concentration of the zinc salt solution in step S3 is 0.001-0.1 mol / L.

[0031] More preferably, the concentration of the zinc salt solution in step S3 is 0.01 mol / L.

[0032] Preferably, the reaction temperature of the ion exchange between the mesoporous NH4Y molecular sieve and the zinc salt solution in step S3 is 60-100°C.

[0033] If the ion exchange time in the zinc salt solution is too long, it will lead to blockage of the molecular sieve pores and a certain etching effect on the molecular sieve surface, which will reduce the specific surface area of ​​the molecular sieve and thus reduce the conductivity of the molecular sieve; if the ion exchange time is too short, the exchange is insufficient, resulting in too little zinc content in the molecular sieve framework, thereby reducing the conductivity of the molecular sieve.

[0034] Preferably, in step S3, the time for the ion exchange reaction between the NH4Y type molecular sieve and the zinc salt solution is 8 to 24 hours.

[0035] Preferably, the drying temperature in step S3 is 80-120° C., and the drying time is 12-24 hours.

[0036] Preferably, the calcination temperature in step S3 is 550-600° C., and the calcination time is 5-6 hours.

[0037] The present invention also protects a zinc-modified mesoporous Y-type molecular sieve, which is prepared by the above preparation method.

[0038] The present invention also protects an electrochemical sensor, which is prepared by the following steps:

[0039] S1. grinding, washing and drying the glassy carbon electrode to obtain a pretreated glassy carbon electrode;

[0040] S2. The zinc-modified mesoporous Y-type molecular sieve material is dispersed in a solvent to obtain a zinc-modified Y-type molecular sieve suspension;

[0041] S3. Take the zinc-modified mesoporous Y-type molecular sieve suspension treated in step S2 and drop it onto the pretreated glassy carbon electrode, air-dry the solvent, and obtain the electrochemical sensor.

[0042] Preferably, the solvent in step S2 is at least one of ethanol, propylene glycol and nafion solution.

[0043] In the process of preparing electrochemical sensors, the appropriate concentration of molecular sieve suspension and the amount of drop coating can make the prepared electrochemical sensor have excellent detection performance. The concentration of the molecular sieve suspension will affect the dispersion state of the ZnY molecular sieve on the electrode. If the concentration of the molecular sieve suspension is too high or the amount of the molecular sieve suspension is too much, the adsorption sites on the electrode will be saturated, which will limit its adsorption and reaction ability to acetaminophen, resulting in a decrease in the detection sensitivity of the sensor; if the concentration of the molecular sieve suspension is too low or the amount of the molecular sieve suspension is too little, there will be fewer adsorption sites on the electrode, and the adsorption and reaction ability to acetaminophen will be weak, thereby reducing the detection sensitivity and accuracy of the electrochemical sensor.

[0044] Preferably, the concentration of the zinc-modified Y-type molecular sieve in the suspension is 10-30 mg / mL.

[0045] Preferably, in step S3, the volume of the zinc-modified mesoporous Y-type molecular sieve suspension dropwise coated onto the pretreated glassy carbon electrode is 15-25 μL.

[0046] The present invention also protects the use of the electrochemical sensor in detecting the content of acetaminophen.

[0047] Preferably, the application is application in detecting the content of acetaminophen in drugs.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] (1) The preparation method of the zinc-modified mesoporous Y-type molecular sieve of the present invention adopts a new template agent and matches a specific raw material ratio, so that the prepared zinc-modified mesoporous Y-type molecular sieve has the characteristics of large specific surface area and high adsorption capacity, which can promote more active sites to participate in the reaction, allowing more target molecules to be quickly adsorbed in a short time; improve the catalytic rate of the reaction, and at the same time modify the metal zinc to the mesoporous Y-type molecular sieve, so that the molecular sieve material has excellent conductivity, and increases its electrocatalytic activity of the working electrode used in the electrochemical sensor. The total specific surface area of ​​the mesoporous Y-type molecular sieve prepared by the preparation method of the present invention is greater than 500m 2 / g, and the total pore volume is greater than 0.2m 3 / g.

[0050] (2) The present invention utilizes the characteristics of the prepared zinc-modified mesoporous Y-type molecular sieve, such as large specific surface area, high pore volume and excellent conductivity, to modify a layer of zinc-modified mesoporous Y-type molecular sieve material on the surface of the glassy carbon electrode, and construct an electrochemical sensor based on the zinc-modified mesoporous Y-type molecular sieve. The electrochemical sensor prepared by the present invention has a wide linear range for detecting acetaminophen, which is 0.066-10000 μmol / L, and a low detection limit, which can reach 0.01 μmol / L. It has excellent sensing characteristics such as detection sensitivity, stability, reproducibility and selectivity, and can realize the accurate determination of acetaminophen in drugs.

[0051] (3) The electrochemical sensor prepared by the present invention is simple to prepare and easy to operate. It can be used to detect the content of acetaminophen in drugs to reduce the detection cost and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is the X-ray diffraction pattern of the mesoporous NaY molecular sieve prepared in Example 1.

[0053] Figure 2 This is a field emission scanning electron microscope image of the mesoporous NaY molecular sieve prepared in Example 1.

[0054] The magnification of Figure (a) is 6000 times, and the magnification of Figure (b) is 25000 times.

[0055] Figure 3 This is the nitrogen adsorption-desorption isotherm of the mesoporous NaY molecular sieve prepared in Example 1, and the inset is the BJH pore size distribution diagram of the molecular sieve.

[0056] Figure 4 Cyclic voltammetry curves of the electrochemical sensors prepared in Example 17(a), Example 22(b) and Example 23(c), respectively, in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen.

[0057] Figure 5 Cyclic voltammetry curves of the electrochemical sensor prepared in Example 17 in 0.1 mol / L PBS solutions containing 500 μmol / L acetaminophen at different pH values.

[0058] Figure 6 Cyclic voltammetry curves of the electrochemical sensor prepared in Example 17 at different scan rates in a 0.1 mol / L PBS (pH=7.0) solution containing 500 μmol / L acetaminophen.

[0059] Figure 7Cyclic voltammetry curves of the electrochemical sensor prepared in Example 17 in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen (a) and in a 0.1 mol / L PBS solution (pH=7) without acetaminophen (b).

[0060] Figure 8 The selectivity of the electrochemical sensor prepared in Example 17 for detecting acetaminophen.

[0061] Fig. 9 Reproducibility of the electrochemical sensor prepared for Example 17 in detecting acetaminophen.

[0062] Fig.10 The electrochemical sensor prepared in Example 17 was used to detect the stability of acetaminophen.

[0063] Fig.11 The differential pulse voltammetry curves of the electrochemical sensor prepared in Example 17 in different concentrations of acetaminophen, and the inset is the linear relationship between the square root of the peak current of the differential pulse voltammetry curve and the square root of the corresponding concentration. DETAILED DESCRIPTION

[0064] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0065] The self-made Bola type surfactant [C5H5-N + -(CH2) 10 -O-(p-C6H4)2-O-(CH2) 10 -N + -C5H5]·2[Br - ] can be synthesized by the following method:

[0066] S1. Dissolve 20 mmol 4,4'-dihydroxybiphenyl in 80 mL anhydrous ethanol containing 20 mmol potassium hydroxide, then slowly add 100 mmol 1,10-dibromodecane under N2 atmosphere, and reflux at 80°C for 20 h. After cooling to room temperature, filter while hot, wash the solid sample repeatedly with hot ethanol several times, and dry it in a vacuum oven at 50°C for 12 h to obtain BrCH2-(CH2)8CH2-O-(p-C6H4)2-O-CH2(CH2)8-CH2Br, denoted as C ph-10 .

[0067] S2. 20mmolC ph-10and 250mmol pyridine were dissolved in a mixed solution of acetonitrile and toluene with a volume ratio of 1:1 (26mL each), refluxed at 70°C for 10h, the product was cooled to room temperature, filtered and collected, washed with ether, and dried in a vacuum oven at 50°C for 12h to obtain a Bola-type surfactant [C5H5-N + -(CH2) 10 -O-(p-C6H4)2-O-(CH2) 10 -N + -C5H5]·2[Br - ], denoted as C ph-10-6 .

[0068] The equipment used in the embodiments of the present invention is as follows:

[0069] D8 Advance X-ray diffractometer, manufactured by Bruker, Germany, was used to detect the X-ray diffraction pattern of the sample;

[0070] SU8220 field emission scanning electron microscope, produced by Hitach, Japan, was used to characterize the structure of the samples;

[0071] Micromeritics ASAP 2460 fully automatic surface area and porosity analyzer BET, manufactured by Micromeritics, USA, was used to detect the nitrogen adsorption and desorption isotherms of the samples;

[0072] CHI660E electrochemical workstation, produced by Shanghai Chenhua Instrument Co., Ltd., was used to detect the content of acetaminophen.

[0073] The raw material information used in the present invention is as follows:

[0074] Acetaminophen standard sample was purchased from Acmec Ltd;

[0075] Compound paracetamol and amantadine tablets were purchased from Enwei Pharmaceutical Co., Ltd.;

[0076] Sodium aluminate was purchased from Aladdin Biochemical Technology Co., Ltd.;

[0077] Zinc chloride, purchased from Merrill Ltd.;

[0078] Phosphate buffer solutions (PBS, 0.1 mol / L) of different pH were prepared with K2HPO4 and KH2PO4 in different proportions;

[0079] All reagents used in the present invention are analytically pure reagents, and solutions are prepared with deionized water.

[0080] (I) Preparation of zinc-modified mesoporous Y-type molecular sieve:

[0081] Example 1

[0082] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve, and the specific preparation steps are as follows:

[0083] S1. 0.43g template (Bola type surfactant C ph-10-6 ) was dissolved in 7.27 g of deionized water, and 0.80 g of sodium hydroxide, 0.33 g of sodium aluminate and 2.45 g of silica sol were added in sequence, and magnetic stirring was performed at 40° C. for 4 h to obtain an aluminosilicate gel, wherein the molar ratio of the silica sol, sodium aluminate, sodium hydroxide, template and water was 3:1:5:0.15:100.

[0084] S2. The aluminosilicate gel obtained in step S1 was transferred to a Teflon-lined stainless steel autoclave, reacted at 130° C. for 36 h, filtered, washed with deionized water and collected, dried at 80° C. for 12 h, and then calcined at 550° C. for 6 h to obtain a mesoporous NaY molecular sieve;

[0085] S3. The mesoporous NaY molecular sieve obtained in step S2 was subjected to ion exchange with 1 mol / L NH4Cl solution at a solid-liquid ratio of 1:20, the reaction temperature was 80°C, the reaction time was 4h, and the above steps were repeated three times to obtain a mesoporous NH4Y molecular sieve; the mesoporous NH4Y molecular sieve was subjected to ion exchange with 0.01 mol / L ZnCl2 solution at a solid-liquid ratio of 1:50, the reaction temperature was 80°C, the reaction time was 24h, the precipitate was collected by centrifugation, dried at 80°C for 12h, and then calcined at 550°C for 6h to obtain the zinc-modified mesoporous Y molecular sieve;

[0086] Among them, the solid-liquid ratio of the mesoporous NaY type molecular sieve to the NH4Cl solution and the solid-liquid ratio of the mesoporous NH4Y type molecular sieve to the ZnCl2 solution in step S3 are both the ratio of the molecular sieve mass to the salt solution volume.

[0087] Figure 1 The X-ray diffraction pattern of the mesoporous NaY molecular sieve prepared in step S1 of this embodiment is shown in FIG. Figure 1 It can be seen that the NaY molecular sieve prepared in Example 1 presents a characteristic diffraction peak of a Y-type molecular sieve in the XRD wide-angle region (2θ is 5° to 50°), and a first-order characteristic diffraction peak in the XRD low-angle region (2θ is 0° to 5°), indicating that the prepared Y-type molecular sieve has a mesoporous structure.

[0088] Figure 2 The field emission scanning electron microscope image of the mesoporous NaY molecular sieve prepared in step S1 of this embodiment is shown in Figure (a) at a magnification of 6000 times and Figure (b) at a magnification of 25000 times. Figure 2It can be seen that the structure of the NaY type molecular sieve prepared in Example 1 is the same as that of the traditional Y type molecular sieve, showing a typical octahedral shape, uniform particle size, and a significantly open pore structure with a rough surface, which increases the specific surface area of ​​the Y type molecular sieve and is beneficial to improving the catalytic rate of the reaction.

[0089] Figure 3 The nitrogen adsorption-desorption isotherm of the mesoporous NaY molecular sieve prepared in step S1 of this embodiment, and the inset is the BJH pore size distribution diagram of the molecular sieve. Figure 3 It can be seen that the nitrogen adsorption and desorption isotherm of the mesoporous NaY molecular sieve prepared in Example 1 has a hysteresis loop when P / P0>0.5, indicating that the prepared Y-type molecular sieve has a mesoporous structure. From the BJH pore size distribution diagram in the illustration, it can be observed that the sample has a narrow peak around 4nm, indicating that the molecular sieve has a uniform mesopore size. At the same time, the pore structure parameters are summarized based on the test results. The total specific surface area of ​​the molecular sieve reaches 745.6021m 2 / g, the total pore volume is 0.299402m 3 / g, the high specific surface area and large adsorption capacity make the molecular sieve have highly exposed active sites, which is conducive to the catalytic reaction.

[0090] Example 2

[0091] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that: in step S1, the amount of template added is 0.287 g, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template and water is 3:1:5:0.10:100, and the total specific surface area of ​​the prepared molecular sieve is 633.6722 m 2 / g, the total pore volume is 0.2238m 3 / g.

[0092] Example 3

[0093] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that: in step S1, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template agent and water is 5:1:5:0.15:100, and the total specific surface area of ​​the prepared molecular sieve is 708.1537 m 2 / g, the total pore volume is 0.2624m 3 / g.

[0094] Example 4

[0095] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that in step S1, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template agent and water is 3:2:5:0.15:100, and the total specific surface area of ​​the prepared molecular sieve is 655.3935 m 2 / g, the total pore volume is 0.2598m 3 / g.

[0096] Example 5

[0097] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that: in step S1, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template agent and water is 3:1:4:0.15:100, and the total specific surface area of ​​the prepared molecular sieve is 594.6568 m 2 / g, the total pore volume is 0.2155m 3 / g.

[0098] Example 6

[0099] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that: in step S1, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template agent and water is 3:1:6:0.15:100, and the total specific surface area of ​​the prepared molecular sieve is 723.9345 m 2 / g, the total pore volume is 0.2813m 3 / g.

[0100] Example 7

[0101] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that: in step S1, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template agent and water is 3:1:5:0.15:80, and the total specific surface area of ​​the prepared molecular sieve is 582.1196 m 2 / g, the total pore volume is 0.2239m 3 / g.

[0102] Example 8

[0103] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that: in step S1, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template agent and water is 3:1:5:0.15:140, and the total specific surface area of ​​the prepared molecular sieve is 673.6394 m 2 / g, the total pore volume is 0.2427m 3 / g.

[0104] Example 9

[0105] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps in Example 1, except that the reaction temperature of the aluminosilicate gel in step S2 is 110°C, and the total specific surface area of ​​the prepared molecular sieve is 689.9564 m 2 / g, the total pore volume is 0.2466m 3 / g.

[0106] Example 10

[0107] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve, and its preparation process is basically the same as the preparation steps of Example 1, except that the reaction temperature of the aluminosilicate gel in step S2 is 150°C. The total specific surface area of ​​the prepared molecular sieve is 713.5821m 2 / g, the total pore volume is 0.2630m 3 / g.

[0108] Embodiment 11

[0109] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve, and its preparation process is basically the same as the preparation steps of Example 1, except that the reaction time of the aluminosilicate gel in step S2 is 24 hours. The total specific surface area of ​​the prepared molecular sieve is 612.3885 m 2 / g, the total pore volume is 0.2129m 3 / g.

[0110] Example 12

[0111] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve, and its preparation process is basically the same as the preparation steps of Example 1, except that the reaction time of the aluminosilicate gel in step S2 is 48 hours. The total specific surface area of ​​the prepared molecular sieve is 676.9159 m 2 / g, the total pore volume is 0.2418m 3 / g.

[0112] Table 1

[0113]

[0114]

[0115] Embodiment 13

[0116] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve, and its preparation process is basically the same as the preparation steps of Example 1, except that: the concentration of the zinc salt solution in step S3 is 0.001 mol / L.

[0117] Embodiment 14

[0118] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve, and its preparation process is basically the same as the preparation steps of Example 1, except that: the concentration of the zinc salt solution in step S3 is 0.1 mol / L.

[0119] Embodiment 15

[0120] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve, and its preparation process is basically the same as the preparation steps of Example 1, except that: in step S3, the time for the ion exchange reaction between the NH4Y-type molecular sieve and the zinc salt solution is 8 hours.

[0121] Example 16

[0122] This embodiment provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve, and its preparation process is basically the same as the preparation steps of Example 1, except that: in step S3, the time for the ion exchange reaction between the NH4Y-type molecular sieve and the zinc salt solution is 16 hours.

[0123] (II) Preparation of electrochemical sensor:

[0124] Embodiment 17

[0125] This embodiment provides an electrochemical sensor, and the specific preparation steps are as follows:

[0126] S1. A glassy carbon electrode with a diameter of 3 mm was polished with 0.3 μm and 0.05 μm Al2O3 polishing powder, the surface was cleaned with deionized water, and then ultrasonicated in deionized water and anhydrous ethanol for 30 min respectively, and dried at room temperature to obtain a pretreated glassy carbon electrode;

[0127] S2. Take 20 mg of the zinc-modified mesoporous Y-type molecular sieve material prepared in Example 1 and disperse it in 1 mL of ethanol and ultrasonicate for 30 min to obtain a uniformly dispersed molecular sieve suspension with a concentration of 20 mg / mL;

[0128] S3. Drop 20 μL of the molecular sieve suspension onto the pretreated glassy carbon electrode obtained in step S1, and naturally air-dry the ethanol at room temperature to obtain the electrochemical sensor based on the zinc-modified mesoporous Y-type molecular sieve.

[0129] Figure 4The cyclic voltammetry curves of the electrochemical sensors prepared in Example 17 (a), Example 22 (b) and Example 23 (c) in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen are shown in FIG. Figure 5 It can be seen that if the amount of molecular sieve suspension applied is too much, the adsorption sites on the electrode will be saturated and the electrochemical response will not change much; if the amount of molecular sieve suspension applied is too little, there will be fewer adsorption sites on the electrode, and the adsorption and catalytic ability of acetaminophen in the solution will be weak, thereby reducing the detection sensitivity and accuracy of the electrochemical sensor.

[0130] Embodiment 18

[0131] This embodiment provides a method for preparing an electrochemical sensor, and its preparation process is basically the same as that of Example 17, except that the zinc-modified mesoporous Y-type molecular sieve material used in step S2 is replaced by the zinc-modified mesoporous Y-type molecular sieve material prepared in Example 13. The electrochemical sensor prepared by this scheme is subjected to cyclic voltammetry test in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen, and the detection current is 46.35 μA.

[0132] Embodiment 19

[0133] This embodiment provides a method for preparing an electrochemical sensor, and its preparation process is basically the same as that of Example 17, except that the zinc-modified mesoporous Y-type molecular sieve material used in step S2 is replaced by the zinc-modified mesoporous Y-type molecular sieve material prepared in Example 14. The electrochemical sensor prepared by this scheme is subjected to cyclic voltammetry test in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen, and the detection current is 72.59 μA.

[0134] Embodiment 20

[0135] This embodiment provides a method for preparing an electrochemical sensor, and its preparation process is basically the same as that of Example 17, except that the zinc-modified mesoporous Y-type molecular sieve material used in step S2 is replaced by the zinc-modified mesoporous Y-type molecular sieve material prepared in Example 15. The electrochemical sensor prepared by this scheme was tested by cyclic voltammetry in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen, and the detection current was 61.28 μA.

[0136] Embodiment 21

[0137] This embodiment provides a method for preparing an electrochemical sensor, and its preparation process is basically the same as that of Example 17, except that the zinc-modified mesoporous Y-type molecular sieve material used in step S2 is replaced by the zinc-modified mesoporous Y-type molecular sieve material prepared in Example 16. The electrochemical sensor prepared by this scheme is subjected to cyclic voltammetry test in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen, and the detection current is 70.52 μA.

[0138] Embodiment 22

[0139] This embodiment provides a method for preparing an electrochemical sensor, and its preparation process is basically the same as that of Example 17, except that the volume of the molecular sieve suspension dripped on the glassy carbon electrode in step S3 is 25 μL. The electrochemical sensor prepared by this scheme is tested by cyclic voltammetry in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen, and the detection current is 70.98 μA.

[0140] Embodiment 23

[0141] This embodiment provides a method for preparing an electrochemical sensor, and its preparation process is basically the same as that of Example 17, except that the volume of the molecular sieve suspension dripped on the glassy carbon electrode in step S3 is 15 μL. The electrochemical sensor prepared by this scheme is tested by cyclic voltammetry in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen, and the detection current is 43.52 μA.

[0142] Embodiment 24

[0143] This embodiment provides an electrochemical sensor, and its preparation process is basically the same as that of Example 17, except that: the concentration of the molecular sieve suspension in step S2 is different, and the concentration is 10 mg / mL. The electrochemical sensor prepared by this scheme is tested by cyclic voltammetry in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen, and the detection current is 55.69 μA.

[0144] Embodiment 25

[0145] This embodiment provides an electrochemical sensor, and its preparation process is basically the same as that of Example 17, except that: the concentration of the molecular sieve suspension in step S2 is different, and the concentration is 30 mg / mL. The electrochemical sensor prepared by this scheme is tested by cyclic voltammetry in a 0.1 mol / L PBS solution (pH=7) containing 500 μmol / L acetaminophen, and the detection current is 74.88 μA.

[0146] Table 2

[0147]

[0148] Comparative Example 1

[0149] This comparative example provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that: in step S1, the amount of template added is 0.143 g, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template and water is 3:1:5:0.05:100, and the total specific surface area of ​​the prepared molecular sieve is 498.3656 m 2 / g, total volume is 0.1639m 3 / g.

[0150] Comparative Example 2

[0151] This comparative example provides a method for preparing a zinc-modified mesoporous Y-type molecular sieve. The preparation process is basically the same as the preparation steps of Example 1, except that: in step S1, the molar ratio of silica sol, sodium aluminate, sodium hydroxide, template agent and water is 1:1:5:0.15:100, and the total specific surface area of ​​the prepared molecular sieve is 452.1655 m 2 / g, the total volume is 0.1229m 3 / g.

[0152] Performance Testing

[0153] (1) Optimization of acetaminophen content detection conditions

[0154] The test was carried out using a three-electrode system of an electrochemical workstation, with the electrochemical sensor prepared in Example 17 as the working electrode, denoted as a ZnY / GCE electrode, a saturated calomel electrode as a reference electrode, and a platinum wire electrode as a counter electrode. Cyclic voltammetry was performed in a PBS buffer solution containing acetaminophen to examine the effects of pH value and scan rate on the acetaminophen current response.

[0155] The electrochemical sensor prepared in Example 17 was placed in a 0.1 mol / PBS buffer solution containing 500 μmol / acetaminophen under different pH conditions. The cyclic voltammetry test curves are as follows: Figure 5 As shown;

[0156] Depend on Figure 5It can be seen that during the oxidation process of acetaminophen, the separation of electrons and protons leads to the formation of its oxidation products. When the pH value is from 5.8 to 7.0, the potential ranges from 0.42V to 0.31V, and the anode peak current gradually increases. When the pH value is from 7.0 to 8.6, the potential ranges from 0.31V to 0.27V, and the anode peak current gradually decreases. The peak potential of the entire process moves toward a negative value, indicating that protons participate in the oxidation process of acetaminophen. From the results, it can be seen that in 0.1mol / LPBS (pH=7.0), the oxidation peak of acetaminophen reaches the maximum current response, that is, the optimal pH value used in the detection is 7.0.

[0157] The electrochemical sensor prepared in Example 17 was placed in a 0.1 mol / L PBS (pH=7.0) solution containing 500 μmol / L acetaminophen. The cyclic voltammetry test curve was as follows: Figure 6 As shown;

[0158] Depend on Figure 6 It can be seen that as the scan rate changes from 40mV / s to 220mV / s, the anode and cathode currents of acetaminophen increase with the increase of the scan rate. In addition, the oxidation peak potential continues to shift positively, and the reduction peak potential shifts negatively. There is a potential difference of 0.16V (<0.2V) between the oxidation peak and the reduction peak of acetaminophen. The results show that acetaminophen is a quasi-reversible redox process on the ZnY / GCE electrode. At the same time, if the scan rate is too slow in the experiment, the reaction time will be longer; if the scan rate is too fast, the instability of the electrode detection process will be enhanced. The optimal scan rate selected in this experiment is 100mV / s.

[0159] (2) Electrochemical performance test of electrochemical sensors

[0160] The three-electrode system of the electrochemical workstation was used for testing. The electrochemical sensor prepared in Example 17 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire electrode was used as the counter electrode. Cyclic voltammetry was performed in a 0.1 mol / L PBS buffer solution (pH=7) containing acetaminophen and a 0.1 mol / L PBS buffer solution (pH=7) not containing 500 μmol / L acetaminophen. The initial potential was 0 V, the scan rate was 100 mV / s, and the sampling interval was 0.001 V. The results are shown in FIG. Figure 7 shown.

[0161] Depend on Figure 7It can be seen that in the blank electrolyte solution without acetaminophen, the working electrode has almost no redox peak. After adding 500 μmol / L acetaminophen, the electrode shows obvious redox peak signal under the potential condition of 0.40V, which has good electrochemical performance and indicates that the reaction process is reversible with good reversibility.

[0162] (3) Selectivity test of electrochemical sensors

[0163] The three-electrode system of the electrochemical workstation was used for testing. The electrochemical sensor prepared in Example 17 was used as the working electrode, denoted as the ZnY / GCE electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire electrode was used as the counter electrode. To a 0.1 mol / L PBS buffer solution (pH=7) containing 500 μmol / L acetaminophen, 50 times the concentration of acetaminophen were added, respectively. 3+ 、Co 2+ , Cu 2+ , K + 、Na + 、Ti 4+ and Zn 2+ The solution was subjected to cyclic voltammetry test to compare the electrochemical response of these interfering substances with acetaminophen solution to verify the selectivity of ZnY / GCE electrode. The test results are as follows: Figure 8 shown.

[0164] Depend on Figure 8 It can be seen that the electrochemical responses of these interfering substances are very weak compared with the electrochemical response of acetaminophen solution, and the detection sensitivity of the modified electrode is much higher than that of the tested interfering substances, indicating that the prepared sensor has good selectivity.

[0165] (4) Reproducibility test of electrochemical sensor

[0166] The three-electrode system of the electrochemical workstation was used for testing. The electrochemical sensor prepared in Example 17 was used as the working electrode, denoted as the ZnY / GCE electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire electrode was used as the counter electrode. In a 0.1 mol / L PBS buffer solution (pH=7) containing 500 μmol / L acetaminophen, the acetaminophen solution was measured multiple times at different times using the same ZnY / GCE electrode and the voltammetric values ​​were recorded to verify the reproducibility of the modified electrode. The test results are shown in FIG. Fig. 9 shown.

[0167] Depend on Fig. 9 It can be seen that the current values ​​measured 8 times have little difference, indicating that the ZnY / GCE electrode has good reproducibility.

[0168] (5) Stability test of electrochemical sensor

[0169] The three-electrode system of the electrochemical workstation was used for the test. The electrochemical sensor prepared in Example 17 was used as the working electrode, denoted as the ZnY / GCE electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire electrode was used as the counter electrode. - 3 mol / L Fe(CN)6 3- / 4- In the presence of 0.1 mol / L KCl solution, 100 fragments were scanned at a scan rate of 100 mV / s, and the stability of the sensor was tested by cyclic voltammetry. The test results are shown in Fig.10 shown.

[0170] Depend on Fig.10 It can be seen that after multiple cycles of scanning, the CV curve of the sensor remains basically unchanged, indicating that the prepared sensor has good stability.

[0171] (6) Detection of acetaminophen standard solutions with different concentrations

[0172] The three-electrode system of the electrochemical workstation was used for testing. The electrochemical sensor prepared in Example 17 was used as the working electrode, denoted as the ZnY / GCE electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire electrode was used as the counter electrode. The 0.1 mol / L PBS solution containing different concentrations of acetaminophen was detected by differential pulse voltammetry. The initial potential was 0 V, the potential increment was 0.004 V, the amplitude was 0.025 V, the pulse width was 50 ms, and the pulse period was 200 ms. The test results are shown in FIG. Fig.11 shown.

[0173] Depend on Fig.11 It can be seen that in the potential range of 0 to 0.7 V, the dotted line is the oxidation peak formed by the blank background curve of the ZnY / GCE electrode. -8 mol / L~1.0×10 -2 mol / L, the peak current increases with the increase of acetaminophen concentration. The inset shows the linear relationship between the peak current and the square root of the corresponding concentration, R 2 =0.9995. The results show that the ZnY / GCE electrode has a wide detection range and a very low detection limit, with a detection range of 6.6×10 -8 mol / L~1.0×10 -2 mol / L, and the detection limit was 0.01μmol / L.

[0174] (7) Detection of acetaminophen content in drugs

[0175] The test was carried out using a three-electrode system of an electrochemical workstation, with the electrochemical sensor prepared in Example 17 as the working electrode, denoted as a ZnY / GCE electrode, a saturated calomel electrode as the reference electrode, and a platinum wire electrode as the counter electrode. The solution prepared from the drug compound acetaminophen amantadine tablets was used instead of the acetaminophen standard solution for detection by differential pulse voltammetry. The test results are shown in Table 3.

[0176] As shown in Table 3, the solution was measured four times in parallel, and the recovery rate was between 96.8% and 101.6%, and the relative standard deviation RSD was 2.1%, indicating that the ZnY / GCE electrode has a high repeatability in determining the content of acetaminophen in actual drugs.

[0177] Table 3

[0178]

[0179]

[0180] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a zinc-modified mesoporous Y-type molecular sieve, characterized in that: The following steps are involved: S1. The silica sol, sodium aluminate, pH regulator and template are mixed in water to obtain an aluminosilicate gel, wherein the template is a Bola-type surfactant [C5H5-N + -(CH2) 10 -O-(p-C6H4)2-O-(CH2) 10 -N + -C5H5]·2[Br - ]; S2. The aluminosilicate gel obtained in step S1 is heated to react. After the reaction is completed, the product is collected by filtration and washing, and the product is dried and calcined to obtain a mesoporous NaY molecular sieve; S3. The mesoporous NaY molecular sieve of step S2 is subjected to ion exchange with an ammonium salt solution to obtain an NH4Y molecular sieve; the NH4Y molecular sieve is subjected to ion exchange with a zinc salt solution, and after the reaction is completed, the precipitate is collected, dried, and calcined to obtain a mesoporous ZnY molecular sieve, which is the zinc-modified mesoporous Y molecular sieve; Among them, the molar ratio of silica sol, sodium aluminate, pH adjuster, template agent and water in step S1 is (2-6):(0.5-3):(2-8):(0.06-0.50):(50-250).

2. The method for preparing the zinc-modified mesoporous Y-type molecular sieve according to claim 1, characterized in that: In the step S1, the molar ratio of silica sol, sodium aluminate, pH adjuster, template agent and water is (3-5):(1-2):(3-6):(0.08-0.30):(80-150).

3. The method for preparing the zinc-modified mesoporous Y-type molecular sieve according to claim 1, characterized in that: The reaction temperature in step S2 is 110-150°C.

4. The method for preparing the zinc-modified mesoporous Y-type molecular sieve according to claim 1, characterized in that: The concentration of the zinc salt solution in step S3 is 0.001-0.1 mol / L.

5. The method for preparing the zinc-modified mesoporous Y-type molecular sieve according to claim 1, characterized in that: In step S3, the time for the ion exchange reaction between the NH4Y type molecular sieve and the zinc salt solution is 4 to 24 hours.

6. A zinc-modified mesoporous Y-type molecular sieve, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 5.

7. An electrochemical sensor, characterized in that: Prepared by the following steps: S1. grinding, washing and drying the glassy carbon electrode to obtain a pretreated glassy carbon electrode; S2. The zinc-modified mesoporous Y-type molecular sieve material according to claim 6 is dispersed in a solvent to obtain a zinc-modified Y-type molecular sieve suspension; S3. Take the zinc-modified mesoporous Y-type molecular sieve suspension treated in step S2 and drop it onto the pretreated glassy carbon electrode, air-dry the solvent, and obtain the electrochemical sensor.

8. The electrochemical sensor according to claim 7, characterized in that: The concentration of the zinc-modified Y-type molecular sieve in the suspension is 10-30 mg / mL.

9. The electrochemical sensor according to claim 7, characterized in that: In the step S3, the volume of the zinc-modified mesoporous Y-type molecular sieve suspension dropwise coated on the pretreated glassy carbon electrode is 15 to 25 μL.

10. Use of the electrochemical sensor according to any one of claims 7 to 9 in detecting the content of acetaminophen.

Citation Information

Patent Citations

  • Mesoporous and microporous MFI type nano molecular sieve with flaky pastry-shaped morphology and preparation method and application thereof

    CN108002402A

  • Small-particle mesoporous Y-type molecular sieve as well as preparation method and application thereof

    CN114132944A

  • Microporous-mesoporous level zeolite material and preparation method therefor and use thereof

    WO2019214022A1